Anti-inflammatory activity of bioaccessible fraction from eryngium foetidum leaves - Suwitcha Dawilai (2018)
Eryngium foetidum (EF) has long been used as a medicinal plant and culinary spice in tropical regions. Phytochemicals in its leaves have been proposed to be responsible for the anti-inflammatory and antioxidant activities. The present study used in vitro digestion coupled with Caco-2 cells to assess such activities. Caco-2 cells were incubated with aqueous fraction from simulated digestion (bioaccessible fraction) of EF leaves with/without bile extract prior to stimulation with interleukin-1 beta (IL-1β). Monocyte chemoattractant protein-1 (MCP-1) and IL-8 in culture media and the intracellular reactive oxygen species (ROS) were measured. Approximately 24% β-carotene and 35% lutein of leaves were present in the aqueous fraction. The transfer of caffeic and chlorogenic acids to the aqueous fraction was 76%-81%, while that of kaempferol was 48%. Prior incubation of Caco-2 cells with the bioaccessible fraction suppressed IL-1β activated IL-8 and MCP-1 by 33%, but the fraction lacking mixed micelles decreased IL-8 and MCP-1 levels only by 11%. The pretreatment of Caco-2 cells with the bioaccessible fraction of EF reduced ROS by 34%; the fraction lacking mixed micelles decreased ROS by 28%. These data suggest that bioactive compounds partitioning in mixed micelles play a significant role to suppress the proinflammatory insult but with a modest antioxidant effect. © 2013 Suwitcha Dawilai et al.